Modeling Fast X-Ray Variability around an Accreting Black Hole - Yejing Zhan; Bei You; Adam Ingram; Wenkang Jiang; Fayin Wang (The Astrophysical Journal)
X-ray interband time lags are observed during the outbursts of black hole X-ray binaries. Timing analysis of fast variability in low Fourier frequency bands shows that high-energy photons lag behind low-energy photons, a phenomenon referred to as hard lag. Conversely, in high Fourier frequency bands, low-energy photons lag behind high-energy photons, known as soft lag. This frequency-dependent lag spectrum suggests that the lags arise from different physical processes. Notably, a trend has been observed wherein the lags shift toward shorter timescales during the rising hard state, indicating an evolution in the inner accretion flow. In this study, we simulate these interband lags by conducting Monte Carlo simulations of the rapid variability within the geometry of a jet base corona. We consider both inward propagating accretion rate fluctuations and reverberation (light-crossing) delays in our simulations. We successfully reproduce both low-frequency hard lags and high-frequency soft lags in a self-consistent manner. We replicate the observed evolution of the frequency-dependent lag spectra by varying the geometrical scale of the corona and the viscous frequency of the disk. Finally, we discuss the potential of a spherical corona and emphasize that polarization observations from the Imaging X-ray Polarimetry Explorer and the enhanced X-ray Timing and Polarimetry mission will be crucial for distinguishing the corona’s geometry in future studies.